ChatGPT and Critical Digital Pedagogy: Examining the Potential and Challenges for Educational Practice - FX. Risang Baskara (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2024)
The infusion of technology in teaching and learning has opened up new ways to engage and educate and stimulated discussions over its role in perpetuating social divides while creating uneven distributions of power. In doing so, this study provides a theoretical lens on the potential ways in which ChatGPT and critical digital pedagogy intersect around technology affordances to support community-engaged, critically oriented teaching practice. Grounded in critical pedagogy and a theoretical framework informed by the basic tenets of ChatGPT, this research seeks to explore how it addresses issues that underpin critically oriented digital teaching practices rooted in dialogue & empowerment, and social justice. This scholarly contribution addresses an existing gap in the literature by exploring the interplay between ChatGPT and critical digital pedagogy, providing discerning contemplations on how technology can stimulate more engaged, vital, and socially equitable educational modalities. Drawing on previous research and methodologies, the present study unpacks associations between ChatGPT and critical digital pedagogy. Key findings from this exploration show ChatGPT as an essential benefit of reflection practices for empowerment and justice in the digital learning area. The implications of these findings are substantial for educators, researchers and policymakers wishing to foster more equitable educational practices in the digital age.